2009
DOI: 10.1152/ajpheart.01342.2008
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of extracellular superoxide dismutase on endothelial function during aging

Abstract: Lund DD, Chu Y, Miller JD, Heistad DD. Protective effect of extracellular superoxide dismutase on endothelial function during aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 29 publications
3
40
0
Order By: Relevance
“…In ecSOD knockout mice, lack of ecSOD has no significant effect on blood pressure under normal physiological conditions; however, lack of ecSOD augments angiotensin II (AII)-induced hypertension and promotes endothelial dysfunction. Endothelial dysfunction, characterized by a lack of dilation of blood vessels in response to endothelium-dependent vasoactive substances, such as acetylcholine, is consistent with a deficiency of bioavailable NO (158,200,266). Recent findings indicate that extracellular alterations in redox potential promote alterations in intracellular redox balance that affect mitochondrial production of ROS (155,184).…”
mentioning
confidence: 99%
“…In ecSOD knockout mice, lack of ecSOD has no significant effect on blood pressure under normal physiological conditions; however, lack of ecSOD augments angiotensin II (AII)-induced hypertension and promotes endothelial dysfunction. Endothelial dysfunction, characterized by a lack of dilation of blood vessels in response to endothelium-dependent vasoactive substances, such as acetylcholine, is consistent with a deficiency of bioavailable NO (158,200,266). Recent findings indicate that extracellular alterations in redox potential promote alterations in intracellular redox balance that affect mitochondrial production of ROS (155,184).…”
mentioning
confidence: 99%
“…Previous work in aged humans and animals has shown that NAD(P)H oxidase contributes to age-related endothelial dysfunction and vascular fibrosis and that reducing SOD1 (cytosolic), SOD2 (mitochondrial), or SOD3 (extracellular) worsens endothelial function with aging (3,4,12,13,19,25). Furthermore, we have previously shown that aortic valve calcification is strongly associated with increases in oxidative stress and reductions in antioxidant defense mechanisms in humans (27), and several studies have shown that the balance between oxidative stress and nitric oxide bioavailability is an important determinant of vascular and valvular calcification in vitro (27,39,41).…”
mentioning
confidence: 99%
“…The third SOD isoform present in the extracellular vasculature, SOD3, protects vascular cells from superoxide-inactivation of endothelial cellular signal NO; SOD3 expression was reported to decrease in aged mice (106). As ROS levels increase in aged tissues, antioxidant machinery becomes even more imperative to manage oxidative stress.…”
Section: Cellular Anti-oxidant Machinerymentioning
confidence: 99%